Disparities and protective factors in pandemic-related mental health outcomes: a Louisiana-based study - Rung, Ariane L.; Oral, Evrim; Prusisz, Tyler; Peters, Edward S. (Frontiers in Public Health, 2024)
Introduction The COVID-19 pandemic has had a wide-ranging impact on mental health. Diverse populations experienced the pandemic differently, highlighting pre-existing inequalities and creating new challenges in recovery. Understanding the effects across diverse populations and identifying protective factors is crucial for guiding future pandemic preparedness. The objectives of this study were to (1) describe the specific COVID-19-related impacts associated with general well-being, (2) identify protective factors associated with better mental health outcomes, and (3) assess racial disparities in pandemic impact and protective factors. Methods A cross-sectional survey of Louisiana residents was conducted in summer 2020, yielding a sample of 986 Black and White adults. The exposure was overall pandemic impact, measured using the Epidemic-Pandemic Impacts Inventory, and the outcome was general well-being (GWB), measured with the General Well-Being Schedule. Potential protective factors included social support, resilience, and social cohesion. Linear regression models were constructed to examine the association between pandemic impact and GWB, with each protective factor added as an effect modifier. These relationships were further assessed for differences by race. Results Pandemic stressors can be grouped into social, health, work, finance, and family-related impacts. Black persons displayed higher levels of pandemic impact as well as lower levels of social support, resilience, and social cohesion (p < 0.0001), highlighting existing racial disparities, though Black respondents and White respondents exhibited no differences in general-well being. Social support, resilience, and social cohesion were identified as protective factors for both groups (p < 0.0001, respectively), but these protective effects deteriorated as pandemic impacts increased. The addition of a pandemic impact by race interaction term was also significant in each model (p = 0.0020, p < 0.0001, and p = 0.0095, respectively) and showed that the protective effects of social support and resilience deteriorated more rapidly for Black persons than White persons, while the protective effects of social cohesion deteriorated more rapidly for White persons than Black persons. Discussion This study emphasizes the importance of psychosocial resources in buffering the mental health impact of pandemics. It also suggests greater vulnerability for marginalized communities lacking access to crucial support systems. Findings underscore the need for targeted interventions that bolster access to social support, promote resilience, and strengthen social cohesion, particularly within minority groups. Additionally, policymakers should consider proactive measures to assist in recovery and mitigate the disproportionate impact of future crises on vulnerable populations.